2012
DOI: 10.1186/1471-2458-12-946
|View full text |Cite
|
Sign up to set email alerts
|

Treatment actions and treatment failure: case studies in the response to severe childhood febrile illness in Mali

Abstract: BackgroundAppropriate home management of illness is vital to efforts to control malaria. The strategy of home management relies on caregivers to recognize malaria symptoms, assess severity and promptly seek appropriate care at a health facility if necessary. This paper examines the management of severe febrile illness (presumed malaria) among children under the age of five in rural Koulikoro Region, Mali.MethodsThis research examines in-depth case studies of twenty-five households in which a child recently exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
(36 reference statements)
3
19
0
Order By: Relevance
“…In a few instances, caregivers were referred to higher level public health facilities for more invasive treatment without any treatment initiated at the primary external source. Thus, similar to what other researchers in sub-Sahara Africa have observed, caregivers in our study vacillated between multiple sources, travelling long distances and incurring numerous costs in an attempt to find a cure [ 32 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a few instances, caregivers were referred to higher level public health facilities for more invasive treatment without any treatment initiated at the primary external source. Thus, similar to what other researchers in sub-Sahara Africa have observed, caregivers in our study vacillated between multiple sources, travelling long distances and incurring numerous costs in an attempt to find a cure [ 32 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…While just under half of the caregivers reported that they did not intend to seek external care when they initiated home management, all caregivers whose child did not improve sought treatment from an external source within the same/next day. The strategy to start with home management allows caregivers to wait in hope the less expensive home medicines will suffice, postponing direct and indirect expenses associated with seeking external treatment [ 32 ]. This approach also enables those wishing to seek further treatment to secure money, liquid assets, or find alternate source of labor to pay for these expenses [ 17 , 31 , 33 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost was a major barrier to seeking treatment in the hospital. 34 In our study (FGDs), cost was considered an issue among the urban poor. They may borrow money to access formal healthcare thus exposing access gaps with their rural counterparts.…”
Section: Knowledge About Immunizationmentioning
confidence: 99%
“…For both groups of women, cost was the most common reason for failing to do so, followed by distance to the health facility (HF) and illness not perceived as serious. 37 In poorresource settings, appropriate treatment is not even guaranteed in the health facilities 18,20,34 and mothers will still consult neighbouring unqualified healthcare providers 38 herbalists and diviners 20 after visiting the HFs. As reported by our urban discussants, fear of fake and substandard drugs drives some mothers to patronize traditional providers whom they consider more trustworthy.…”
Section: Knowledge About Immunizationmentioning
confidence: 99%